Crescentic IgA nephropathy with preserved renal function - Macau,Ricardo A (2017)
Crescentic glomerulonephritis is a severe form of glomerular inflammation. IgA nephropathy (IgAN) is the most common primary glomerulonephritis and rarely presents as crescentic glomerulonephritis with rapidly progressive glomerulonephritis. Treatment of IgAN includes renin-angiotensin system blockade and immunosuppression in select cases with persistent proteinuria and/or renal failure, which are also indications for biopsy. Prognosis markers guide treatment and crescents are recognized as an indication of powerful immunosuppression as they are associated with rapid decline of renal function. We describe a case of crescentic IgA nephropathy with preserved renal function that was associated with several episodes of severe tonsillitis. Renin-angiotensin system blockade and corticosteroids were used and renal function remains stable. To our knowledge, this is the third case described in the literature of a patient with crescents and IgA glomerular deposition but with preserved renal function. A more benign aspect of crescents and association with tonsillitis episodes may explain a more favorable prognosis